The Importance and Performance of Different Dimensions of the Experience Based Model within Cultural Institutions - Brzovska, Ezheni (Athens Journal of Tourism, 2018)
Research interest in cultural marketing has increased significantly in recent years, due to numerous changes in the environment. The experience economy as an emerging concept is employed across a wide range of industries, which indicates the need to implement the model in different consumption situations. The goal of this paper is to evaluate the importance and performance of different activities within the experience economy utilized to create and deliver visitors’ experiences in cultural institutions. The paper analyzes whether the pertinent activities of the experience economy model are of equal importance for different audiences. The Kruskal – Wallis test was employed to reveal the statistically significant differences between certain dimensions of the experience-based model regarding gender, age, education and income of the respondents. The research results will provide interesting and important insights for arts managers and marketers to improve the effectiveness and efficiency in enticing and retaining audiences by employing the experience economy and increase customer value for specific target groups.
Keywords: cultural institution, demographic characteristics, experience economy.